POLA KOMUNIKASI INTERPERSONAL ORANG TUA DAN ANAK DALAM MEMAHAMI BAHAYA GADGET (Studi Kasus Desa Bandar Khalipah Kecamatan Percut Sei Tuan) - Aulia, Mega Putri; Ritonga, Sakti (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
This research examines how parents and children communicate about gadget threats in Bandar Khalipah Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. Children in Bandar Khalipah Village grow hooked to devices since they don't realize the risks and have little parental supervision. Bandar Khalipah Village parents provide kids electronics due to busyness and contemporary necessities. In this setting, parents must talk with their children about device threats. This study employs descriptive qualitative methods. collecting data via interviews, observation, and documentation. Data validity was checked via triangulation. This research found that democratic parents communicate with their children via openness and mutually established regulations. Parents directly compliment their kids' deeds. Parents and children engage closely with electronics. Avoiding gadgets in early life, educating children about their effects, and setting a positive example in gadget usage are all strategies to comprehend the harmful effects of gadget use on children.